Thermodynamic-based method for supporting design and operation of thermal grids in presence of distributed energy producers - Catrini Pietro; Tancredi Testasecca; Maurizio La Villetta; Massimo Morale; Antonio Piacentino (Journal of Sustainable Development of Energy, Water and Environment Systems, 2023)

(untitled)
District heating networks are well-established technologies to efficiently cover the thermal demand of buildings. Recent research has been devoting large efforts to improve the design and management of these systems for integrating low-temperature heat coming from distributed sources such as industrial processes and renewable energy plants. Passing from a centralized to a decentralized approach in the heat supply, it is important to develop indicators that allow an assessment of the rational use of the available heat sources in supplying heating networks, and a quantification of the effect of inefficiencies on the unit cost of heat. To answer these questions, Exergy Cost Theory is here proposed. Thanks to the unit exergetic cost of heat, energy managers can (i) quantify the effects of thermodynamic inefficiencies occurring in the production and distribution on the final cost of heat, (ii) compare alternative systems for heat production, and (iii) monitor the performance of buildings’ substation over time. To show the capabilities of the method, some operating scenarios are compared for a cluster of five buildings in the tertiary sector interconnected by a thermal grid, where heat is produced by a cogeneration unit, an industrial process, and distributed heat pumps. Results suggest that moving from the centralized production of heat based on fossil fuels to a decentralized production with air-to-water heat pumps, the unit cost of heat can be decreased by almost 30% thanks to the improvement of thermodynamic efficiency. In addition, the analysis reveals a great sensitivity of unit exergetic cost to the maintenance in substations. The developed tool can provide thermodynamic-sound support for the design, operation, and monitoring of innovative district heating networks.